Knowledge and beliefs about HPV among college students in Vietnam and the United States. Issue 1 (January 2018) - Kamimura, Akiko; Trinh, Ha N.; Weaver, Shannon; Chernenko, Alla; Wright, Lindsey; Stoddard, Mary; Nourian, Maziar M.; Nguyen, Hanh
Abstract: Any sexually active person has the possibility of contracting the human papillomavirus (HPV) sometime in their lifetime. HPV vaccines are effective in preventing HPV if obtained prior to viral exposure. Research on knowledge and beliefs of HPV and HPV vaccination among college students in Vietnam is significantly scarce. The purpose of this study is to examine the knowledge and beliefs about HPV among college students in Vietnam compared to college students in the US. This cross-cultural comparison will fill a void in current research on this subject. Over 900 college students ( N = 932: n = 495 in Vietnam and n = 437 in the US) participated in a self-administered survey on the knowledge and beliefs about HPV in September and October 2016. Vietnamese participants reported lower levels of knowledge and experiences with the HPV virus and vaccines ( p < 0.01). Additionally, Vietnamese participants also exhibited more barriers in obtaining the vaccination, as well as, HPV risk denial ( p < 0.01). The level of knowledge is an important predictor of barriers ( p < 0.01; η p 2 = 0.022 ) and risk denial ( p < 0.01; η p 2 = 0.116 ). On average, both Vietnamese and US participants could correctly answer less than half of the survey questions regarding HPV knowledge. Additionally, provider recommendations are potentially more important than informal connections (e.g. friends, family) to reduce barriers to HPV vaccination ( p < 0.01; η p 2 = 0.035 ) and denial of HPV risks ( p < 0.05; η p 2 = 0.008 ). The increase of knowledge about HPV prevention, including and vaccination, has the potential to be improved through provider interventions. Vietnam could take action toward promoting HPV vaccinations not only at an individual level but also at a national or local level. Further research may examine the effects of a lack of knowledge on HPV-related health outcomes.